2008
DOI: 10.1523/jneurosci.1929-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Organization of Human Cortical Networks in Health and Schizophrenia

Abstract: The complex organization of connectivity in the human brain is incompletely understood. Recently, topological measures based on graph theory have provided a new approach to quantify large-scale cortical networks. These methods have been applied to anatomical connectivity data on nonhuman species, and cortical networks have been shown to have small-world topology, associated with high local and global efficiency of information transfer. Anatomical networks derived from cortical thickness measurements have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

76
1,032
6
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,139 publications
(1,134 citation statements)
references
References 55 publications
76
1,032
6
5
Order By: Relevance
“…Bassett et al, 2008), and they may become important diagnostic tools in future clinical applications of the connectome.…”
Section: Brain Structural Network Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Bassett et al, 2008), and they may become important diagnostic tools in future clinical applications of the connectome.…”
Section: Brain Structural Network Analysismentioning
confidence: 99%
“…Schizophrenia and Alzheimer's disease are the two most prominent examples (Bassett et al, 2008;Buckner et al, 2009). In both cases it has been shown that widespread changes in cortical thickness, white matter structure, brain electrophysiology and metabolism occur and are hypothesized to be related to changes in the underlying connectivity, which likely precisely translates into the related cognitive impairment.…”
Section: Neuro-science Questions That May Benefit From Connectomicsmentioning
confidence: 99%
“…The description of the large-scale human brain organization has allowed studying the hypothesis that some neuropsychiatric disorders are related to disarrays of connectivity between cortical areas. Indeed, aberrant structural patterns have been verified in the brain organization of subjects with autism, schizophrenia, depression, anxiety disorders, Alzheimer's disease and frontotemporal dementia (Supekar et al, 2008;He et al, 2008;Bassett et al, 2008;Bassett and Bullmore, 2009;Lynall et al, 2010;Menon, 2011). Revealing these disorder related differences has improved the understanding of how dysfunction of cognitive and emotion regulation processes are related to the altered brain network organization.…”
Section: Introductionmentioning
confidence: 99%
“…In case of schizophrenia in general, data obtained from fMRI suggest that cortical networks of schizophrenic adults are less small-world type, less hierarchical, less clustered, less efficiently wired (Bassett et al, 2008;Bullmore and Sporns, 2009) and have a less hub-dominated configuration (Lynall et al, 2010). Moreover, Basset et al (Bassett et al, 2008) showed that multimodal network organization of patients with schizophrenia are abnormal, presenting increased connection distance and reduced hierarchy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation